2016
DOI: 10.1039/c6dt00045b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hydrogen storage properties of the 2LiBH4–MgH2composite with BaTiO3as an additive

Abstract: The 2LiBH4-MgH2 + 20 wt% BaTiO3 composite was prepared by ball-milling LiBH4, MgH2 and BaTiO3, and the effect of BaTiO3 on the hydrogen storage properties of the composite was investigated. TG-DSC results show that the onset dehydrogenation temperature of the composite is 299 °C, which is 124 °C lower than that of 2LiBH4-MgH2, and the dehydrogenation amount of the composite increases from 6.86 wt% to 7.48 wt% at 500 °C. Kinetic tests show that the dehydrogenation amount of 2LiBH4-MgH2 + 20 wt% BaTiO3 reaches 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Research efforts have been focused on developing and verifying onboard automotive hydrogen storage materials to meet these targets. Many kinds of complex materials have been synthesized and studied for storing a high capacity of hydrogen, such as amide/imide systems like LiNH 2 /Li 2 NH, complex metal hydrides like LiAlH 4 and NaAlH 4 , and borohydrides like LiBH 4 , NaBH 4 , and Mg­(BH 4 ) 2 . However, these materials require improvements of the properties for development as practical materials. For instance, the amide/imide systems form byproduct gas during dehydrogenation, complex metal hydrides are not easily reversible, and borohydrides have sluggish kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Research efforts have been focused on developing and verifying onboard automotive hydrogen storage materials to meet these targets. Many kinds of complex materials have been synthesized and studied for storing a high capacity of hydrogen, such as amide/imide systems like LiNH 2 /Li 2 NH, complex metal hydrides like LiAlH 4 and NaAlH 4 , and borohydrides like LiBH 4 , NaBH 4 , and Mg­(BH 4 ) 2 . However, these materials require improvements of the properties for development as practical materials. For instance, the amide/imide systems form byproduct gas during dehydrogenation, complex metal hydrides are not easily reversible, and borohydrides have sluggish kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…[104] With BaTiO 3 as an additive, the onset dehydrogenation temperature was decreased by 124 ºC. [105] Upon dehydrogenation, BaTiO 3 reacted with LiBH 4 forming BaB 6 and TiO 2 . BaB 6 is beneficial to lower the stability of LiBH 4 , whereas TiO 2 has a catalytic effect in improving the kinetics of hydrogenation/dehydrogenation.…”
Section: Catalyst Doping Into Reactive Compositesmentioning
confidence: 99%
“…One of the most effective strategies to improve the hydrogen storage performance of 2LiBH 4 -MgH 2 composite is the introduction of metal-based catalysts, including metal halides, metal oxides, and metal sulfides. Induced by the high reactivity of MgH 2 and LiBH 4 , these metal-based catalysts would be transformed to stable metallic borides in general, which are able to reduce the operating temperature and simultaneously promote the kinetics of hydrogen desorption and adsorption process of 2LiBH 4 -MgH 2 composite. For instance, it has been demonstrated that the formation of CoB from the interaction between Co and LiBH 4 plays a catalytic role in improving the H 2 desorption and adsorption of 2LiBH 4 -MgH 2 and promoting the formation of MgB 2 , which results in the reduction of incubation period down to only 4 h . Interestingly, during the dehydrogenation process of Ni-catalyzed 2LiBH 4 -MgH 2 composite, the formation of MgNi 3 B 2 is identified as the heterogeneous nucleation sites for the formation of MgB 2 , which could also facilitate the dehydrogenation kinetics of 2LiBH 4 -MgH 2 composite .…”
Section: Introductionmentioning
confidence: 99%